The Acceptance of Islamic Banking Products in Libya: A Theory of Planned Behavior Approach - Albashir, Walid Ali; Zainuddin, Yuserrie; Panigrahi, Shrikant Krupasindhu (International Journal of Economics and Financial Issues, 2018)
The purpose of this paper is to identify key factors affecting acceptance level of Islamic banking customers in Libya. Despite of growth of Islamic banking all over the world, it is still underdeveloped financial sector in Libya. Libyan customers are unaware of Islamic banking and are unable to make decision on the acceptance of Islamic banking. We suggest a modified theory of planned behaviour model including perceived risk as an important ingredient to customer decision making process. The model is tested against a sample of 293 banking customers using self-administered survey questionnaire. The quantitative results revealed that subjective norm and perceived behavioural control are more significant to increase intention to use Islamic banking. Customer attitude and perceived risk was found to have no significant influence on intention to accept Islamic banking at 0.05 level. This research suggests that Islamic banks need to develop effective marketing strategy emphasizing on sharia instrument like Islamic assurance and beliefs along with perceived risk to satisfy the value of potential customers. As an implication, focusing on risk management while providing quality information to the customers towards Islamic banking products will lead to increase customer’s intention. Keywords: Islamic Banking, Theory of Planned Behavior, Behavioral Intention, Perceived Risk, Customer Involvement JEL Classifications: C3, G41, O33